Design, trajectory generation and control of quadrotor research platform - Salunkhe D.H.; Sharma S.; Topno S.A.; Darapaneni C.; Kankane A.; Shah S.V. (My University, 2025)
We describe the modeling, estimation and control of a quadrotor in 3D environment using the 3DR Pixhawk PX4 as controller through Robot Operating System(ROS). The paper discusses a method to measure moment of inertia of quadrotor about its principal axes to achieve better results in an inexpensive way. We also present the trajectory generation and segment optimization of the trajectory commanded to the quadrotor. We describe a method of controlling the quadrotor through ROS by providing necessary inputs to the flight controller using the built-in firmware. © 2016 IEEE.